At her pleasure: Black women writing sexual desire. (1st September 2022) - Montlouis-Gabriel, Johanna
Abstract : Black women's bodies and sexualities have particularly been exposed and spoken about in public spaces from an outsider perspective. In this essay, I ground the exploration of sexual pleasure as described and imagined by Black female characters in contemporary short stories written by Black French women. I examine three short stories from the anthology Volcaniques: Une anthologie du Plaisir (2015) by Gisèle Pineau, Léonora Miano, and Hemley Boum to explore how these writers complicate, expand, and subvert heteronormative notions of pleasure, and seek it via their Black female characters. Instead of further silencing Black women's sexuality for fear of reinscribing hypersexual tropes, or reiterating narratives of trauma and unhappy sexualities, these narratives reclaim women's bodies and sexualities for their pleasures. I take an intersectional and afrofeminist approach to underscore the different forms of sexual (and other forms of) pleasure for middle-class Black French women. These narratives prove to be a mirror for other Black women who read and experience pleasure as well as a window to the variety of ways they experience and write about (sexual) pleasure and desire. Ultimately, beyond body and sexual positivity, by writing about these sexual matters, these compelling narratives lay claim to the humanity of middle-class Black women.